Effect of the COVID-19 Pandemic on the Labor Market in 2020 - Trostel, Philip (Maine Policy Review, 2021)
The disruption of the labor market caused by the COVID-19 pandemic was unprecedented. The unemployment rate in February 2020, just before the pandemic spread to the United States, was 3.5 percent nationally and 3.2 percent in Maine; two months later, the unemployment rate jumped to 14.8 percent nationally and 10.4 percent in Maine. Although usually changes in the unemployment rate reliably indicate changes in the health of economy, that was not the case during the COVID-19 pandemic. The harm to the labor market in 2020 was even worse than indicated by the dramatic increase in unemployment. In addition to the unprecedented spike in unemployment, there was an unprecedented decrease in labor force participation. There were also an important increase in absence from work and an important decline in average weekly hours of work among those employed. This article takes an in-depth look at these trends both nationally and in Maine.
Keywords: Maine; labor force participation; unemployment reasons; work hours